Del amor al odio… Las críticas soviéticas al maoísmo. Un primer balance - Jaime Ortega Reyna; Ricardo Yanuel Fuentes (Nuevo mundo - Mundos Nuevos)
In this work, we intend to review the materials translated into Spanish and produced specifically by the Soviet intelligentsia regarding what began to be called Maoism. Beyond the debates and the printed material derived from the partisan life of each Communist Party in the world, from Moscow, from the sixties and especially in the seventies, numerous publications circulated under the editorial seals of Progreso and the RIA Novosti News Agency. Texts that reported on the phenomena associated with the Chinese revolution in a critical and rather acidic way. Our analysis revolves around the following questions: What was it that the Soviet works later disseminated to the Spanish-speaking public questioned? How did they characterize what was happening in the nation that was once their ally? What was their definition of Maoism? Did the debate reach truly irreconcilable theoretical positions? Thus, the objective of our essay is to briefly present an analysis of the various works published in the Soviet Union criticizing Maoism to understand the vision that the Soviets built and projected on the Chinese and their ideas around the world.